Students' Critical Thinking Ability in Understanding Natural Science Problems: Systematic Literature Review - Tasya Dian Muliana; Ivayuni Listiani; Marheny Lukitasari (International Journal of Technology and Education Research, 2025)
Developing critical thinking skills in the science learning process, students are expected to have an active attitude in identifying science problems. The aim of this research is to develop learning activities on critical thinking skills in solving students' science problems. This research uses the SLR method which is carried out by: (1) identification; (2) assess; (3) interpret all existing research evidence by studying indicators; and (4) how to bring out students' critical thinking skills in science as a research object. So that this understanding can be used to solve problems and make decisions for the progress of human civilization. The conclusions in this research are: (1) differences in indicators used to measure students' critical thinking abilities; (2) differences in aspects of interpretation indicators; (3) use of PBL; and (4) STEAM approach.